2021
DOI: 10.1002/nag.3308
|View full text |Cite
|
Sign up to set email alerts
|

A poromechanical‐damage‐based‐model for water‐driven fracture modeling of concrete gravity dams

Abstract: Water‐driven fracture propagation is a fundamental issue in the failure analysis of cracked concrete gravity dams. In the present paper, a poromechanical‐damage–based model is proposed to study the water‐fracture interaction in saturated porous media in order to highlight the importance of considering the presence of the pressurized water in propagating fractures. The solid behavior is described by a plastic damage model. The crack openings computation is performed using a post‐processing method combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It found that the application of coupled model could better reflect load‐deformation characteristics of concrete under high pore water pressure. The Reference [69] also considered the importance of water‐driven microcrack extension in the study of cracked concrete gravity dams and proposed a model based on pore mechanics damage. It shows that deeper and larger microcracks would occur and continue to expand when the existence of pressurized water is considered.…”
Section: Effect Of Water Pressure On Concrete Strengthmentioning
confidence: 99%
“…It found that the application of coupled model could better reflect load‐deformation characteristics of concrete under high pore water pressure. The Reference [69] also considered the importance of water‐driven microcrack extension in the study of cracked concrete gravity dams and proposed a model based on pore mechanics damage. It shows that deeper and larger microcracks would occur and continue to expand when the existence of pressurized water is considered.…”
Section: Effect Of Water Pressure On Concrete Strengthmentioning
confidence: 99%
“…Concrete damaged plasticity has been widely used and is recognized with high-reliability in the failure analysis of concrete behavior under complex conditions. Several failure analyses of concrete structure have been carried by the concrete damage model coupled with Plasticity in previous researches [23,24]. Nowadays, relevant development and improving were made in order to control and optimization of plastic deformation in concrete damage plasticity model [25,26].…”
Section: Plastic Damage Model For Nonlinear Behavior Of Concretementioning
confidence: 99%
“…Transport of mass, heat, or electric charge through heterogeneous solid material is an important problem in a number of practical applications. A large number of experimental and numerical works concerning heterogeneous materials are devoted to study the transport of moisture or water, 1,2 heat, 3,4 or chlorides 5,6 . Particularly in civil engineering, the transport behavior of concrete is of paramount importance as temperature, relative humidity, and/or chemical substances largely influence its mechanical behavior as well as durability 7 …”
Section: Introductionmentioning
confidence: 99%